CLINICAL EFFICACY OF MINIMALLY INVASIVE INTERVENTIONS IN THE TREATMENT OF BILITY PERITONITIS AS A COMPLICATION OF OPERATIONS FOR CHOLELITHIASIS - Halima Ikramdjanovna, Kariyeva (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study analyzed 49 cases of bile peritonitis caused by bile leakage after bile duct surgeries, aiming to identify causative factors and assess the effectiveness of various treatments. Postoperative bile peritonitis incidence was found to be 0.8%, with "small" bile duct injuries accounting for 57.2% and main bile duct damage contributing to 42.8%. Methods: Diagnostic and therapeutic approaches included ultrasound-guided punctures, transduodenal endoscopic interventions, and laparoscopic techniques. Cases of main bile duct damage identified within 48 hours were treated with high-precision Roux-en-Y gastrointestinal anastomosis (GEA). Results: Minimally invasive methods effectively avoided relaparotomy in 93.3% of patients with "small" bile duct injuries. In contrast, early detection and surgical precision in managing main bile duct injuries provided optimal outcomes, emphasizing the criticality of timely intervention. Novelty: This study highlights the significant role of minimally invasive techniques and early detection in managing bile peritonitis, reducing the need for relaparotomy, and improving patient outcomes. The findings underscore the utility of combining advanced diagnostic and surgical strategies for bile duct injuries.